Analysis of Sport Values Based on Gender at SMPN 50 Kota Bandung - Al Ghazaly, Muhammad Dzikry Abdullah; Septian, Regi Dwi; Riansyah, Riansyah; Yusoff, Yusandra Md (Universitas Pendidikan Indonesia (UPI), 2023)
The aim of this research is to find out the difference between sport values and gender in SMP Negeri 50 Kota Bandung. The survey was conducted on 330 students in the eighth grade of Public Junior High School 50 Bandung City. There were 203 samples with 85 (42%) male respondents and 118 (58%) female respondents. The research method used in this study is a quantitative method with a descriptive survey type of research. The instrument used in this research is a questionnaire or questionnaire. The test instruments are surveys and questionnaires consisting of 30 questions, which were developed by Whitehead. The results obtained show that there are differences in sport values for gender at SMPN 50 Kota Bandung